Genetic parameters and yield potential of Indonesian soybean varieties (Glycine max L.) in wetland during dry season - Ridara, Fadila; Fitriani, Riska; Algina, Azka; Ustari, Debby; Karuniawan, Agung (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Cultivating soybean in wetland areas presents unique challenges, particularly during water-limited conditions like dry season, where yield performance can vary significantly among genotypes. This research aimed to assess the yield potential of Indonesian soybean varieties in wetland during dry season, to estimate genetic parameters, and to determine the relationship among traits. Twenty soybean genotypes were evaluated using Randomized Complete Block Design (RCBD) with three replications. Yield components measured included seed weight per plot, number of seeds per plant, and overall yield potential (tons per hectare). The results revealed significant variation among the genotypes. The estimation of genetic parameters indicates that traits comprising plant height, 100-seed weight, and the number of seeds per plant have high heritability and significant CVG/CVP ratios, suggesting efficient genetic selection potential and opportunities for genetic improvement through breeding. Pearson’s correlation network plot shows positive associations between traits, including plant height (PH), weight of biomass (WB), weight of seed per plot (WSP) and yield. 'Deja 1' variety exhibited the highest yield potential at 1.75 tons per hectare, while 'BS 99' variety showed the lowest at 0.18 tons per hectare. These findings underscore the importance of genotype selection in enhancing soybean productivity in water-limited environments. The study offers valuable insights for future breeding programs aimed at improving soybean yields in challenging conditions, such as dry season in wetlands, thereby contributing to sustainable agricultural practices in Indonesia.